2009
DOI: 10.1097/brs.0b013e3181a3c742
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Vertebral Compression Fractures

Abstract: VP and KP are 2 minimally invasive procedures that have been shown to be effective in the treatment of symptomatic vertebral compression fractures. Although the incidence of adverse events for both VP and KP are low, it appears that VP is associated with a statistically significant increased rate of procedure-related complications and cement extravasation (symptomatic and asymptomatic). Future prospective studies with large patient enrollment will be needed to further validate the finding of this meta-analysis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(122 citation statements)
references
References 6 publications
3
105
2
5
Order By: Relevance
“…In contrast, the BKP arm yielded more consistent results. The lower rate of cement extravasation after BKP is consistent with previous studies [15,18,[49][50][51][52]. A number of factors may have contributed to the heterogeneity in the VP group: procedural technique, variation in considering extravasation as a complication [51], different postoperative radiological follow-up (plain films vs. computed tomography [51,53]), cement viscosity (inverse relationship [52]), cement pressure [49], fracture level (higher extravasation rates above T7), and cement volume (dose dependent [54]).…”
Section: Cement Extravasationsupporting
confidence: 86%
“…In contrast, the BKP arm yielded more consistent results. The lower rate of cement extravasation after BKP is consistent with previous studies [15,18,[49][50][51][52]. A number of factors may have contributed to the heterogeneity in the VP group: procedural technique, variation in considering extravasation as a complication [51], different postoperative radiological follow-up (plain films vs. computed tomography [51,53]), cement viscosity (inverse relationship [52]), cement pressure [49], fracture level (higher extravasation rates above T7), and cement volume (dose dependent [54]).…”
Section: Cement Extravasationsupporting
confidence: 86%
“…In prospective studies, the medical complications, symptomatic cement leakage, and mortality all occurred in less that 1% of patients each. (25) Asymptomatic cement leakage in osteoporotic fractures was seen as high as 21% and 7% for vertebroplasty and kyphoplasty, respectively. New fracture risk was similar to that observed in this meta-analysis, ranging 16% to 18%.…”
Section: Discussionmentioning
confidence: 99%
“…3 A meta-analysis of complications from BKP in cancer patients showed that the 2 main complications were cement extravasation (rarely symptomatic) and adjacent-level VCF, which occurred in 6.1% and 16% of patients, respectively. 14 The purpose of our investigation was to describe a new complication secondary to BKP that we characterize as "tumor extravasation." This phenomenon has been largely discussed as a theoretical complication, but no reports have been published until now.…”
Section: Discussionmentioning
confidence: 99%